Pedestrian friendly grade separated pedestrian crossing - Mohamad Azril Bin Mohamad Anuar, Mohamad Azril (2009)
The idea is instead the pedestrian going above the vehicle, why doesn't vehicle go up above the pedestrian. This new crossing design is to eliminate pedestrian vertical movement, give short crossing distance and give less crossing time for the pedestrian, motorcyclist and bicyclist.